Water for Life: Water for Life - Matteucci, Magda Beatriz de Almeida (Scientific Journal ANAP, 2025)
Objective - The objective of this study was to access the sensitivity and understanding of commitments to the possibility of human future survival on the planet considering the use of water. Methodology - A questionnaire was applied to a group of 50 students of the Agronomy course at the Federal University of Goiás. Two open-ended questions were asked: Name 4 (four) individual alternatives and 4 (four) collective alternatives for water management. Originality/relevance - Water is the main resource for the existence of life on the planet, so it is essential to conserve and save it, thus, water management measures are essential to achieve this objective. Results - The results were subjected to univariate analysis. From the individual alternatives, 29 solutions were obtained and from the collective alternatives, 31, which were classified into two groups: changes in attitude and use of technologies. A broader approach to the responses was to consider nature-based solutions - NBS (3 solutions found) and Water Management in the city (6 suggestions found). Of all the ones that presented the highest frequency were: using gray water/reused water (20.12%), using rainwater (17.23%), environmental education (16.5%), short showers/reducing shower time (13.45) and protecting/recovering springs/watersheds (13.0%). Social and environmental contributions - The volume of water used by humans has been increasing over the years (LIMA, 2001). Billions of people still live without safely managed water and sanitation (UN, 2025). And planning solutions for the rational use of water requires the integrated solutions proposed here.